Fibroblasts modulate epithelial cell behavior within the proliferative niche and differentiated cell zone within a human colonic crypt model - Massaro, Angelo; Villegas Novoa, Cecilia; Wang, Yuli; Allbritton, Nancy L. (Frontiers in Bioengineering and Biotechnology, 2024)
Colonic epithelium is situated above a layer of fibroblasts that provide supportive factors for stem cells at the crypt base and promote differentiation of cells in the upper crypt and luminal surface. To study the fibroblast-epithelial cell interactions, an in vitro crypt model was formed on a shaped collagen scaffold with primary epithelial cells growing above a layer of primary colonic fibroblasts. The crypts possessed a basal stem cell niche populated with proliferative cells and a differentiated, nondividing cell zone at the luminal crypt end. The presence of fibroblasts enhanced cell differentiation and accelerated the rate at which a high resistance epithelial cell layer formed relative to cultures without fibroblasts. The fibroblasts modulated cell proliferation within crypts increasing the number of crypts populated with proliferative cells but decreasing the total number of proliferative cells in each crypt. Bulk-RNA sequencing revealed 41 genes that were significantly upregulated and 190 genes that were significantly downregulated in cocultured epithelium relative to epithelium cultured without fibroblasts. This epithelium-fibroblast crypt model suggests bidirectional communication between the two cell types and has the potential to serve as a model to investigate fibroblast-epithelial cell interactions in health and disease.